Estándares de calidad para la inclusión en la educación inicial - Tipantasig Chiliquinga, Lilian Carola (2025)
This review article aimed to analyze the achievements of quality standards in initial education in children up to 5 years of age with special educational needs in Ecuador, by compiling studies and research from different educational centers in the national territory of the last five years. The most relevant results are: the teaching and administrative staff know the quality standards of initial education, but only a percentage of 25% to 40% have the skills to work in the classroom with children who have special educational needs. They are responsible for a large number of students that does not allow them to develop differential activities and they do not know what curricular adaptations can be applied in these cases. There is no support from tutors or specialized shadow teachers, lack of interactions with public and private companies that favor these inclusive teaching processes, there are in certain short periods for the preparation of thesis, projects that are not permanent, with respect to the standard relationship of the educational center with the community, children with special educational needs (SEN) do not have transportation or food provided by the institutions, and although they have student counseling, it is not replicated in all educational centers in the country. The article concludes that inclusive education in Ecuador still has a long way to go to guarantee that children with different special needs achieve the desired significant learning, which provides them with dignity and Ecuadorian educational equity.